La economía mixta en el socialismo liberal - Kamichi Miyashiro, Manuel José (2022)
The present essay aims to contribute to the debate on whether the mixed economy can be compatible with a system of liberal socialism. That is, if the coexistence of private and public agents in the economy can promote a model that is based on the development of individual freedoms and equal opportunities. For this reason, a historical review was carried out in the political and economic field to look for both theoretical and empirical background of experiences on this subject. First showing the compatibility between liberalism with socialism, and later, describing mixed economies such as China, France, Argentina and the United States in specific stages of their economic growth. Finally, complement with other suggestions so that a complete economic system typical of liberal socialism can be formed.